Quantifying increases in problem behavior following downshifts in reinforcement: A retrospective analysis and replication. Issue 1 (9th May 2022) - Falligant, John M.; Hagopian, Louis P.; Kranak, Michael P.; Kurtz, Patricia F.
Abstract : The recurrence of a previously eliminated or reduced behavior following a downshift in alternative reinforcement is referred to as resurgence. Resurgence as Choice (RaC) is a quantitative model of behavioral persistence that posits that resurgence is governed by the same behavioral principles that underlie choice behavior. Consistent with the predictions of RaC, extant basic research with animals indicates that resurgence increases as an exponential function of the size of the downshift in alternative reinforcement. Recently, Shahan and Greer (2021) extended this finding to resurgence of problem behavior during schedule thinning following functional communication training (FCT). They found that when resurgence occurred, it increased exponentially as a function of relative decrements in reinforcer availability during schedule thinning with compound schedules of reinforcement. The purpose of the current study was to directly replicate the analytic procedures described in Shahan and Greer to examine resurgence of problem behavior during schedule thinning following FCT using two novel clinical datasets. Our results closely replicate the findings from Shahan and Greer, providing additional support for the generality of resurgence during downshifts in alternative reinforcement in clinical contexts. These results also highlight the potential applicability of RaC for modeling resurgence of problem behavior during FCT schedule thinning.